The Effect of Ergonomic Gymnastics “Kandiha Weki” on Foot Sensivity And Sugar Levels in DM Patients In The Working Area of East Bolo Community Health Center - Nurwahidah,; Syaiful,; Imam Fadhlullah Pratama,; Annisa Dwi Kemalahayati,; M.Fahrurrahman,; Sri Yuliana,; Imam Fajlurrahman, (International Journal of Scientific Research and Management (IJSRM), 2025)
Diabetes mellitus is a hyperglycemic disease characterized by the absolute absence of insulin or a relative decrease in cell insensitivity to insulin. Type 2 DM constitutes 90% of all diabetes mellitus categories. Diabetes mellitus is a fairly high cause of death, due to complications that cause atherosclerosis, coronary heart disease and stroke. The research design was quasi-experimental, using a pre-test and post-test with control group design. Using Wilcoxon and Mann Whitney tests. The sampling technique was purposive sampling with a sample of 100 respondents. The results of data analysis using the Wilcoxone test in the treatment group showed a p-value of 0.000 (p